O real do egresso do sistema prisional: circulação de normas, valores e vulnerabilidades - Carolyne Reis Barros (2011)
This research have the intuit to grasp through the action-research and interviews in depth, the real lived by egresses from the penitentiary system, that is, legal/illegal rules, implicit/explicit with circulating on what we call of vulnerability zone of pósprision. Our subjects of research are egresses from Association for Protection and Assistance to Convicteds (APAC) of Santa Luzia MG how lived a history as egress from common prison system and, prisoners of this institutions how was ex-prisonersfrom others prisons unit. The theoretical base used on this research was the Marginal Realism, inside of Critical Criminology, as the theory that illegitimate the penal system and the Ergology as the perspective that looks in dialectical perspective way on human activity and a ethical posture in front of this research and in front of the subjects. This posture is oriented for the horizontality between the knowledge that circulate on research and on the intellectual discomfort front the inexhaustibility of real. So, we emphasize some situations lived by the egresses: the indelible marks left by the prison, like the prisionalization, shame situations, prejudice, stigma, and humiliation, gets interlaced on daily, the family relation, with the State and whit drugs involving the use and commerce. Those elements are constituted like challenges tolegally life, calling the egresses to a discussion of norms, and a world of values that exceeds the abstract norms, the statistics and the profiles. Lastly, this research intend denunciate that the social reintegration is a challenge, a fight that egress faces daily, because of the concretes conditions of life doesn`t offers different possibilities of life in crime. Based on this failure to deal with the "crime" through the criminaljustice system and prison, we engage on fight for different ways to deal with the conflict in society and for the overcoming of penal system and your prisons.